Republic of Palau : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines recent economic developments in the Republic of Palau. Palau has made a modest recovery in 2000 and 2001. Real GDP growth has been about 1 percent in 2000 and 2001, after the recession brought about by the Asian crisis reached its trough of negative 5 1\2 percent growth in 1999. This recovery was mainly owing to grant-financed large infrastructure projects. However, the outlook on tourism, Palau's major industry, remains weak owing to the events on September 11, and the expected El Nino, which also threaten the development of tourism-related private sector projects.